DEVELOPMENT OF TARGET MARKETS THROUGH THE UTILIZATION OF MINI LATHE IN MOTORCYCLE WORKSHOPS IN TASIKMALAYA CITY - Arisman, Ari; Patimah, Titin (Inaba of Community Services Journal, 2023)
The purpose of this Community Service activity is to provide an understanding of the development of the target market through the use of technology in the form of mini lathe machines for motorcycle repair shops in Tasikmalaya City. This activity is like counselling and assistance to business actors who are the main resource in services so that it can create business growth, especially from the marketing aspect. Equipment and supplies are also provided by the proposer to expedite the process of implementing this community service activity by providing a tutorial on using a mini lathe machine. The number of activity participants was 9 people including partners who are business actors in the field of motorbike repair services/services in the City of Tasikmalaya. Participants enthusiastically took part in the series of activity events and felt happy because they could develop types of services for their businesses by utilizing new technology in the form of using mini lathes.